POTATO VARIETIES PROMISING FOR BREEDING TARGETED AT COMMERCIAL TRAITS - L. I. Kostina; O. S. Kosareva (Труды по прикладной ботанике, генетике и селекции)
The article presents the results of studying VIR’s potato collection. Following such study, the best cultivars of potato are recommended as source material for breeding programs targeted at basic commercial traits, such as high yield, starch content, resistance to late blight (Phytophthora infestans (Mont.) de Bary) and Ro1 pathotype of golden potato cyst nematode (Globodera rostochiensis (Woll.) Behr.). Described here are the cultivars combining resistance to gold potato cyst nematode with other valuable commercial traits. The identified genotypes are recommended to be included in potato breeding programs.